"Cardio‐Neuromodulation" With a Multielectrode Irrigated Catheter: A Potential New Approach for Patients With Cardio‐Inhibitory Syncope. (1st August 2016) - DEBRUYNE, PHILIPPE
"Cardio‐Neuromodulation": A New Syncope Treatment: Syncope is frequently neurally mediated and can seriously affect quality of life. Different ablation strategies have been successfully performed. These approaches have not gained wide acceptance and are quite extensive and complex, exposing patients to significant risks. This article reports the case of a 16‐year‐old girl who was severely affected by frequent and prolonged episodes of syncope and was treated by tailored ablation of the anterior right ganglionated plexus with a multielectrode irrigated catheter. She had fainted >30 times in the 5 years preceding treatment, experiencing approximately 10 severe episodes of syncope in the previous 12 months. After 3 minutes of ablation, the P‐P interval was reduced by >400 milliseconds. Syncope disappeared and the patient has remained completely asymptomatic over a follow‐up of 22 months. The "reset" basal P‐P interval has remained unchanged (follow‐up electrocardiogram at 16 months). At 6 months, there was no residual heart rate activity <50 bpm. On 24‐hour rhythm registration, P‐P intervals ≥1, 000 milliseconds (corresponding to a heart rate of ≤60 bpm) were reduced by >16, 000 beats. We believe that this case report is original for several reasons: the unusual clinical presentation; the unique structure targeted; the very limited ablation, implying much lower risks for the patient; the anatomical approach; and the different endpoint. This new "cardio‐neuromodulation" approach could be useful for the treatment of patients with neurally mediated syncope.